2004
DOI: 10.1179/096805104225004004
|View full text |Cite
|
Sign up to set email alerts
|

Enzymology of lipid A palmitoylation in bacterial outer membranes

Abstract: The enzymology of palmitate addition to lipid A can be traced to the early discovery of monosaccharide lipid A precursors, but the functional importance of lipid A palmitoylation in bacterial resistance to the host immune response has emerged only recently. Lipid A palmitoylation in enterobacteria is determined by a PhoP/PhoQ-activated gene pagP, which encodes an unusual outer membrane enzyme of lipid A biosynthesis. PagP structure and dynamics have now been elucidated by both NMR spectroscopy and X-ray crysta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…The transcription profiles between the parental CFT073 strain and the phoP mutant were compared from aerated, mid‐exponential‐phase cultures in LB medium (OD 600 = 0.6). We reasoned this would identify genes regulated directly or indirectly by PhoP because (i) LB medium is sufficiently Mg 2+ ‐limited to activate phoPQ ‐dependent gene expression (Garcia Vescovi et al ., 1996; Bishop et al ., 2004; Jia et al ., 2004), and (ii) each phoP ‐dependent phenotype was tested using bacteria cultured under these growth conditions. The microarray analysis showed that deletion of phoP resulted in the differential expression of 620 genes ( P < 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…The transcription profiles between the parental CFT073 strain and the phoP mutant were compared from aerated, mid‐exponential‐phase cultures in LB medium (OD 600 = 0.6). We reasoned this would identify genes regulated directly or indirectly by PhoP because (i) LB medium is sufficiently Mg 2+ ‐limited to activate phoPQ ‐dependent gene expression (Garcia Vescovi et al ., 1996; Bishop et al ., 2004; Jia et al ., 2004), and (ii) each phoP ‐dependent phenotype was tested using bacteria cultured under these growth conditions. The microarray analysis showed that deletion of phoP resulted in the differential expression of 620 genes ( P < 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…PagP enzyme is a ␤-barrel outer membrane protein from Escherichia coli. It catalyzes the palmitate transfer from a phospholipid to a glucosamine unit of a lipid in the outer leaflet and reinforces the outer leaflet to protect E. coli from a host's immune response (19)(20)(21). PagP remains dormant when the outer membrane permeability barrier is intact but can respond adaptively and instantaneously to perturbations to restore the permeability barrier (22).…”
Section: Weakly Stable Regions In the Tm Domain And Stabilization By mentioning
confidence: 99%
“…Palmitate from a phospholipid is incorporated into lipid A by the outer membrane enzyme PagP. 41 The pagP gene was first identified in a Salmonella mutant that was found to be sensitive to cationic antimicrobial peptides (CAMPs), which are included among the products of the TLR4 signal transduction pathway. 13 Consequently, the modification of lipid A with a palmitate chain appears, remarkably, to both attenuate the production of CAMPs through the TLR4 pathway, and protect the bacterial pathogen from the antimicrobial products of that same pathway.…”
Section: Resultsmentioning
confidence: 99%